Eyewitness Accounts on Climate Variability and the Responses: Perspectives from Farmers - Poudel, Jiban Mani (Dhaulagiri Journal of Sociology and Anthropology, 2012)
People with different socio-cultural arrangements havedifferent experiences and responses to climatic variability. The place specific experiences and responses at community level still remain a little explored issue in the discourse of climate change research. This paper deals with local experiences of climatic variability which have been monitoring by locals in their lifetime, on the one hand, and, on the other, explore their responses or coping mechanisms which they have been practicing to mitigate with climatic risks. Moreover, farmers’ experiences were documented in term of observed climatic variability in their lifetime focusing on qualitative data. I have used eyewitness accounts and hearsays to document their experiences of climatic variability. Moreover, farmers have developed various coping mechanisms such as indigenous knowledge, utilize kinship based social network, environment friendly cropping practices, and use of alternative sources of water (water-tanker, well-water) for irrigation, arrange rain-making ritual to cope with climatic uncertainty in their lifetime. DOI: http://dx.doi.org/10.3126/dsaj.v5i0.6362 Dhaulagiri Journal of Sociology and Anthropology Vol. 5, 2011: 171-90